Sentir@Ser - Socio-emotional skills program in a school grouping - Jesus, Ana Salomé; Carvalho, Luísa (Aprender, 2025)
Socio-emotional education in the school context is extremely important for students' all-round development, covering emotional, social and cognitive aspects. Various studies have highlighted the benefits of this approach, which go beyond academic performance, promoting well-being and the ability to face challenges. Bearing this relevance in mind, and taking into account recommendations from different studies, to create an ‘integrated strategy to promote socio-emotional competences’, some schools have been designing and implementing programs in this area. This article, which takes the form of an experience report, is divided into two parts: the first provides a brief review of the literature, and the second presents the Sentir@Ser programme implemented at Agrupamento de Escolas de Arronches, which aims to promote social and emotional skills through mindfulness practices. This program, aimed at children and young people from pre-school to the 9th year of schooling, also includes teaching and non-teaching staff. It features a diverse set of projects and activities tailored to the recipients and their specific objectives. Its implementation has shown very positive results in terms of personal and social development and emotional well-being.
Keywords: socio-emotional competences; schools; students; mindfulness